2006
DOI: 10.1007/s11104-006-9089-0
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of systemic resistance and growth promotion of Arabidopsis thaliana by PGPRs from Nicotiana glauca: a study of the putative induction pathway

Abstract: The ability of six putative plant growth promoting rhizobacteria, isolated from the rhizosphere of Nicotiana glauca L., to stimulate growth and induce systemic resistance against Xanthomonas campestris CECT 95 in Arabidopsis thaliana L. Col-0 was evaluated. The six bacterial strains significantly reduced the disease symptoms caused by the pathogen compared to the controls, with the best results obtained with the Bacillus strain N11.37 and the Stenotrophomonas strain N6.8. These two strains were tested on A. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…The bacterial strains used in this study have demonstrated their ability to produce siderophores and chitinases in vitro, traits related to induction of systemic resistance (van Loon et al, 1998) and have a well contrasted ability to enhance protection in different plant species like tomato (Ramos Solano et al, 2010b), Arabidopsis thaliana (L.) Heynh (Brassicaceae) (Domenech et al, 2007) and soybean (Algar, 2011). This broad spectrum recognition was identified as an asset in this study and the six strains were tested on a different plant species H. perforatum obtaining positive results as expected in growth (Figure 1) and phytopharmaceuticals (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial strains used in this study have demonstrated their ability to produce siderophores and chitinases in vitro, traits related to induction of systemic resistance (van Loon et al, 1998) and have a well contrasted ability to enhance protection in different plant species like tomato (Ramos Solano et al, 2010b), Arabidopsis thaliana (L.) Heynh (Brassicaceae) (Domenech et al, 2007) and soybean (Algar, 2011). This broad spectrum recognition was identified as an asset in this study and the six strains were tested on a different plant species H. perforatum obtaining positive results as expected in growth (Figure 1) and phytopharmaceuticals (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…All six strains were identified by 16s rDNA sequencing: N6.8 as Stenotrophomonas maltophilia, N17.35 as Pseudomonas aeruginosa, N19.27 as P. corrugate, N5.18 as Stenotrophomonas maltophilia, N21.4 as P. fluorescens and N11.37, the only gram positive, as Bacillus subtilis (Ramos Solano et al, 2010b). All of them showed their ability to enhance defense in Solanum lycopersicum plants (Ramos Solano et al, 2010b) and in Arabidopsis thaliana (Domenech et al, 2007) (Table 1).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…f In vitro plant growth promotion effect of two strains was determined using Arabidopsis thaliana Col 0 (Domenech et al, 2007). 100 ml suspension (10 8 cfu/ml) of strain YC6887 or YC6898 was mixed with 1 kg of soil prior to transfer of the two weeks old seedlings of Arabidopsis.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were placed at 4 o C for 2 days as dormant releasing, sown on Petri dishes containing MS medium and placed in a growth chamber at 21 o C with an alternation 12 h photoperiod of light and dark. Plant growth promotion was determined as described previously (Domenech et al, 2007). Both strains were grown in marine broth (Difco) overnight at 30 o C. After centrifugation for 10 min at 9,000 g, the bacterial cells were re-suspended in 10 mM MgSO 4 solution and the concentration was adjusted to 10 8 colony forming units (cfu)/ml (which corresponded to an optical density at 595 nm of 0.3).…”
Section: Methodsmentioning
confidence: 99%
“…These results also show that the induction of systemic resistance in Arabidopsis by GF19-1 does not follow the same pathways involved in ISR that are mediated by rhizobacteria P. fluorescens WCS417r, one of the most widely studied PGPF on Arabidopsis 1 , or the pathways mediated by T. asperellum T203 in cucumber plants 18 . However, the role of SA in the induction of systemic resistance by certain other PGPF remains to be clarified 8,37 . Thus, the signaling pathway elicited by GF19-1 closely resembles the pathway of SAR.…”
Section: Discussionmentioning
confidence: 99%